Bortezomib Inhibits Multiple Myeloma Cells by Transactivating ATF3 to Trigger miR-135a-5p- Dependent Apoptosis - Lai, Xiaolan; Huang, Chuanqian; Nie, Xuekun; Chen, Qi; Tang, Yirong; Fu, Xianguo; Lin, Ying; Nie, Chengjun; Xu, Xinyu; Wang, Xiukang; Chen, Renli; Chen, Zichun (Frontiers in Oncology, 2021)
Multiple myeloma (MM) is a malignant cancer with an increasing in incidence that can be alleviated through bortezomib (BTZ) treatment. Activating transcription factor 3 (ATF3) plays a major role in cancer development. Moreover, microRNAs (miRNAs) regulate carcinogenic pathways, apoptosis, and programmed necrotic cell death. However, the detailed mechanism by which ATF3 modulates BTZ drug sensitivity/resistance remains elusive. In the current study, expression of ATF3 was significantly increased under BTZ treatment in a dose-dependent manner in MM cell lines. In addition, ATF3 could regulate cell apoptosis under BTZ treatment. The effect of ATF3 was negatively regulated by its binding miRNA, miR-135a-5p. When either ATF3 was silenced or miR-135a-5p mimics were added to MM cells, they partially lost sensitivity to BTZ treatment. This was accompanied by low levels of Noxa, CHOP, and DR5, and a decrease in mitochondrial membrane potential. These results revealed the combinatorial regulatory patterns of ATF3 and miR-135a-5p in the regulatory protein interactome, which indicated a clinical significance of the miR-135a-5p-ATF3 protein interaction network in BTZ therapy. This study provides potential evidence for further investigation into BTZ resistance.